Tourist Loyalty Analysis: The Influence of Service Quality and Emotional Value - Dwi Rahmawati, Esti; Singgih Purnomo; Osman, Sharina; Fadila, Sarah; Baaq, Shalli Habiibika (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The research paper examines the interplay between service quality, emotional value, and tourist loyalty within the tourism sector, which significantly contributes to the global economy. Utilising Structural Equation Modeling-Partial Least Squares (SEM-PLS) for data analysis, the study involved 100 respondents who visited Kebumen's Menganti Beach. Findings reveal that service quality positively influences emotional value, which in turn significantly affects tourist loyalty. Specifically, 60.6% of tourist loyalty can be attributed to both service quality and emotional value. The research underscores that high-quality service enhances emotional experiences, fostering stronger connections between tourists and destinations, thereby promoting repeat visits. The study concludes that emotional value is a vital yet often neglected factor in developing strategies to enhance tourist loyalty.